Faith and money how religion contributes to wealth and poverty - Keister, Lisa A., 1968- (New York : Cambridge University Press, 2011)
"For those who own it, wealth can have extraordinary advantages. High levels of wealth can enhance educational attainment, create occupational opportunities, generate social influence, and provide a buffer against financial emergencies. Even a small amount of savings can improve security, mitigate the effects of job loss and other financial setbacks, and improve well-being dramatically. Although the benefits of wealth are significant, they are not enjoyed uniformly throughout the United States. In the United States, because religion is an important part of cultural orientation, religious beliefs should affect material well-being. This book explores the way religious orientations and beliefs affect Americans' incomes, savings, and net worth"--Provided by publisher.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Wealth -- Religious aspects; Wealth -- United States; Money -- Religious aspects; Money -- United States; United States -- Religion; SOCIAL SCIENCE / Sociology / General; RELIGION / Sexuality & Gender Studies; Electronic books